In-situ performance test and simulation of an air source heat pump - Baik, YJ; Chang, YS; Kim, Y (JAPAN SOC MECHANICAL ENGINEERS, 2000)
In this study, in-situ performance test of a 20 RT (70 kW) air-to-air heat pump which has a feature of recovering ventilation energy is carried out. Since test conditions such as indoor and outdoor air conditions cannot be controlled to satisfy the standard test conditions, experiments are done with the inlet air conditions as they exist. From the experimental data obtained with the non-standard test conditions, simulation program is developed to estimate the performance of standard test conditions. The map-based compressor model, epsilon -NTU method with the assumption of refrigerant-side mixed and air-side unmixed and necessary parameters determined from the measurements are used. From the simulation, performance of a large capacity air source heat pump for various conditions and effects of ventilation are calculated. This study provides method of predicting the performance of air source heat pumps in which in-situ performance test is necessary.
Keywords: FLOW